Fentanyl enhances immune cell response through TLR4/MD-2 complex - Chemello, Chiara; Facci, Laura; Marcolin, Emma; Ramaschi, Giovanni Eugenio; Barbierato, Massimo; Giusti, Pietro; Bolego, Chiara; Zusso, Morena (Frontiers in Pharmacology, 2024)
Opioids have been shown to induce neuroinflammation and immune cell activation, that might contribute to some of the opioid side effects, such as opioid-induced tolerance and paradoxical hyperalgesia. In this context, TLR4/MD-2 complex has been proposed as an off-target site for opioid action. This study was aimed at investigating the effect of fentanyl on lipopolysaccharide (LPS)-induced TLR4/MD-2 activation in rat primary microglia and human monocyte-derived macrophages (MDM).The effect of fentanyl was first explored by measuring the expression and release of different proinflammatory mediators in primary rat microglia and human MDM by real- time PCR and ELISA. Then, the involvement of TLR4/MD-2 signaling was investigated studying NF-κB activation in HEK293 cells stably transfected with human TLR4, MD-2, and CD14 genes (HEK-Blue hTLR4 cells) and in human MDM.Results. Fentanyl increased mRNA levels, as well as the LPS-induced secretion of proinflammatory mediators in primary microglia and MDM. Two inhibitors of TLR4/MD-2 signaling, namely the oxazoline derivative of N-palmitoylethanolamine (PEA-OXA) and CLI-095, blocked the production and release of proinflammatory cytokines by microglia stimulated with LPS and fentanyl, suggesting that TLR4/MD-2 could be the target of the proinflammatory activity of fentanyl. Finally, we showed that fentanyl in combination with LPS activated NF-κB signaling in human MDM and in HEK-Blue hTLR4 cells and this effect was blocked by inhibitors of TLR4/MD-2 complex.Discussion. These results provide new insight into the mechanism of the proinflammatory activity of fentanyl, which involves the activation of TLR4/MD-2 signaling. Our findings might facilitate the development of novel inhibitors of TLR4/MD-2 signaling to combine with opioid-based analgesics for effective and safe pain management.